Pemanfaatan Limbah Oli Sebagai Bahan Bakar Pada Penambalan Ban Motor Solusi Mengurangi Konsumsi Spritus Melalui Metode Destilasi - Diana Novitasari (Universitas Katolik Widya Karya Malang, 2023)
Waste oil treatment through the distillation method with the addition of sulfuric acid and sodium hydroxide media was successfully carried out. The purpose of this study was to obtain quality diesel fuel, study the effect of the concentration of chemical media used, and determine the effectiveness of using spritus substitute fuel. Waste oil treatment is carried out using a distillation method that involves the process of precipitation, filtration and addition of acid and alkaline media. After going through the processing process, the resulting products are analyzed and tested physically and chemically such as density, specific gravity, flash point, fire point, calorific value, and kinematic viscosity. The results of physical test research and parameters were obtained at optimum conditions of use using H2SO4 and NaOH concentrations of 6%. Physical tests obtained brownish-yellow fuel while parameter tests on density tests were 817 km/m3, specific gravity was 0.801, flash point and fire point were 61Â°C and 72Â°C,while kinematic viscosity was 4.99 m2/s. The results of this test show that the fuel obtained tends to have diesel quality, so that the fuel has the potential and effectiveness to be used as a substitute for spritus in patching motorcycle tires